Leading while Black in suburbia: a courageous autoethnography - Stubblefield, David (Kansas State University, 2022)
There is a significant need to add to the scholarship of Black male leadership in suburbia. This is a courageous autoethnography that tells my counter-story in an effort to spark courageous conversations about leading while Black in the suburbs. Autoethnography, a research approach about the experiences of the researcher guides the methodology for the study. Autoethnography is an approach to research and writing that seeks to describe and systematically analyze (graphy) personal experience (auto) in order to understand cultural experience (ethnography) (Ellis, Adams, & Bochner, 2011). Utilizing Counter-storytelling, I will take you on a journey of my past experiences that will start a courageous conversation (Singleton, 2015) on Black leadership in suburbia and add to the minimal research in this area of academia. In my story, I utilize critical race theory and deep equity work to help construct deeper meaning and knowledge around the experience of Black male leaders in mostly affluent and mostly white suburban schools. This autoethnography utilizes my self-reflection and writing to explore how my personal experiences are used to connect my counter-story to a wider cultural, social understanding and meaning. I generate autoethnographic narratives on the three research questions that will become chapters of their own. My identity as a Black man and the way it has influenced my experiences in creating inclusive and culturally responsible school culture as a building leader and as a district leader is woven in with the research to generate a courageous conversation about Black male leadership in the suburbs.
Keywords: Leading; Black; Suburbia; Autoethnography; Counter-story; Critical